KAJIAN EROSI, ALIRAN PERMUKAAN DAN KEHILANGAN HARA PADA TANAMAN KELAPA SAWIT DENGAN UMUR YANG BERBEDA Study of Erosion, Runoff and Nutrient Losses from Oil Palm Plantation with Different Ages - journal, Admin (AgriPeat, 2019)
ABSTRACTErosion brings more fertile soil layers, rich in organic matter and nutrients causing loss of plantnutrients. The research aims to study the amount of surface runoff, erosion and nutrient loss in oilpalm plantations of different ages. This research was conducted at PT. Kalimantan Hamparan Sawit,Gunung Mas Regency, lasted for 4 months from May to August 2018. The method used wasmeasurement on an erosion plots of 15mx25m size, covering the amount of erosion, surface runoff andnutrient analysis in the laboratory. The results showed surface runoff on palm oil for 3 years, greaterthan palm oil for 5 years for each rainfall events. The surface flow in 3-year palm is 1.90mm and 5-year palm is 1.50 mm. The average erosion in 3-year palm is 0.07 tons ha-¹, whereas for 5-year palm is0.05 tons ha-¹. The total N-loss in surface runoff in 3-year palm is 0.0036 kg ha-¹ and 5-year palm is0.0017 kg ha-¹. P-available at 3-year palm at 0,0005 kg ha-¹, while 5-year palm at an average of0,0004 kg ha-¹. K loss in 3-year palm is 0.0292 kg ha-¹ and 5-year palm is 0.0108 kg ha-¹. Nutrientloss in erosion in oil palm for 3 years is greater than oil palm in 5 years. The total N-loss in 3-yearpalm is 13.53 kg ha-ha and in 5-year palm is 11.94 kg ha-¹. The 3-year palm oil P is 1.05 kg ha-¹,while the 5-year palm oil is 0.90 kg ha-¹. K loss in 3 years oil palm was 2.54 kg ha-¹ and 5 years palmoil was 2.42 kg ha-¹.Keywords: Runoff, erosion, oil palm, nutrient